ORGANIZATON OF THE ACCOUNTING OF INTANGIBLE ASSETS ON THE BASIS OF INTERNATIONAL STANDARDS OF FINANCIAL REPORTING - Pardaeva Zulfizar Alimovna (PT ANTIS International Publisher, 2024)
This article expresses opinions on the organization of an accounting system based on international financial reporting standards (IFRS) and the organization of accounting for intangible assets based on the requirements of international financial reporting standards, the methodology for their recognition and assessment in the Republic of Uzbekistan